Adaptive-Moodle: Adaptatividade e Interoperabilidade em Ambientes de e-learning utilizando Tecnologias da Web Semântica - Mota, José dos Reis (2010)
Adaptive systems in the field of e-learning are those capable of adapting the content and mode of presentation according to the profile of a particular user or user group. These systems generally remain in the context of academic research and are rarely used in real situations. Moreover, the e-learning environments that present a complete platform of tools and resources available are largely used by educational institutions, but are not adaptive. We propose to integrate these two types of systems, aiming to take advantage of both - adaptivity coupled with the scope of use of e-learning environments. Therefore, we describe the implementation of an agent that integrates an intelligent adaptive system with the e-learning environment Moodle. Furthermore, we design and implement an adaptive system based on ontologies and e-learning standards. We hope to contribute to making e-learning environments best suited to provide meaningful learning, as well as to facilitate the creation of courses, to enable the sharing of learning resources between different systems through semantic web technologies.